(untitled) (Medical Forum Monthly, 2020)
Objective: To quantify the satisfaction fostered after counseling and association of outcomes in alleviation of pre-operative and post-operative anxiety, discomfort and risk apprehension whilst increasing the overall satisfaction among the cataract patients. Study Design: Retrospective study Place and Duration of Study: This study was conducted at the Bodla Eye Care, Multan and Multan Medical and Dental College, Multan from January 2019 to July 2019. Materials and Methods: The study includes seventy patients from South Punjab with Pre-operative cataract. Out of these patients thirty-five were provided with the counseling services in addition to their routine treatment and were allocated as intervention group. The other thirty-five respondents were offered the routine clinical treatment but no counseling and were designated as control group. Results: Prior and after the surgery, patients from intervention group employed convalescent sequel in terms of anxiety (P < .01) and their current satisfaction with experience (P < .01) together with the cooperativeness, which was found substantial in the intervention group, depicting the p <.01. On the contrary, patients in the intervention group had insignificant results in discomfort, risk apprehension and sleep quality in comparison to the respondents of the control group. Conclusion: This causal study indicated to us that recruitment of an assigned counselor could significantly enhance patient’s satisfaction and reduce patients’ pre-operative anxiety, discomfort and risk apprehension levels. It emphasizes the relevance of patient education and counseling in a cataract surgery setting. This could help to improve overall patient satisfaction by meeting his informational needs.